E-health care information systems an introduction for students and professionals - Tan, Joseph K. H. (Jossey-Bass, 2005)
E-Health Care Information Systems is a comprehensive collection written by leading experts from a range of disciplines including medicine, health sciences, engineering, business information systems, general science, and computing technology. This easily followed text provides a theoretical framework with sound methodological approaches and is filled with numerous case examples.
Includes bibliographical references and indexes. - Print version record
Keywords: Medical informatics; Medical telematics; Public health -- Information services; Medicine -- Communication systems; Information storage and retrieval systems; Computer networks; Diagnosis -- Data processing; Delivery of Health Care -- methods; Information Systems; Computer Communication Networks; Diagnosis, Computer-Assisted; Organizational Case Studies; Public Health Informatics; Médecine; Informatique; Télématique médicale; Santé publique; Services d'information; Médecine; Systèmes de communication; Systèmes d'information; Réseaux d'ordinateurs; Diagnostics; Informatique; LANGUAGE ARTS & DISCIPLINES; Library & Information Science; General; Diagnosis; Data processing; Medicine; Communication systems; Public health; Information services; Gesundheitsinformationssystem; Krankenhausinformationssystem; Aufsatzsammlung